High Strain Rate And Quasi-Static Compressive Failure Of Unidirectional Hybrid Kenaf Glass Fibre-Reinforced Composites - Anorhisam, Megat Naiman Megat (Universiti Sains Malaysia, 2021)
Recently, hybrid composites have been critical in the manufacturing operations. Hybrid composites are being used in various applications due to their improved mechanical properties. This study assesses the mechanical properties and damage behaviours of kenaf and glass hybrid composites. Kenaf fibre and Kenaf/glass hybrid composites are the two types of specimens used in this project. The samples were subjected to two different types of compressive loading: quasi-static and high strain rate loading. A high-speed camera was used to capture the moment of failure within the fibre reinforced polymer during the failure analysis. The failures causes are then investigated further using a scanning electron microscope to determine the fracture morphology and type of damage that occurred. This study provides a thorough examination of the failure process as well as damage propagation. The main findings from the literature and compressive testing on the characteristics of the Kenaf fibre and Kenaf/Glass hybrid composites are compared and discussed.